1999
DOI: 10.1093/jnci/91.9.796
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Brush Biopsies and Detection of Nasopharyngeal Cancer in a High-Risk Population

Abstract: Demonstration of EBV DNA in nasopharyngeal brush biopsy specimens detects NPC with a sensitivity of at least 90% (95% confidence interval = 89.63%-91.32%) and a specificity of approximately 99% (95% confidence interval = 98.64%-98.68%). This technique merits further testing as a possible ambulatory screening strategy in high-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 32 publications
5
52
1
2
Order By: Relevance
“…Of nine patients with recurrent or residual disease, only two patients were positive for EBV; therefore, scarring change after irradiation may reduce the overall ability of nasopharyngeal brushing to detect EBV positivity in patients with recurrent NPC. 25 However, the fact that 98% of the swab samples obtained successfully from the nasopharynx contained sufficient DNA for the amplification of the LMP-1 gene did not appear to be a problem in this study. One reason for this phenomenon may be that radiation-treated patients were encouraged to irrigate their nasopharynx vigorously, even during radiation treatment, to prevent crust formation.…”
Section: Discussionmentioning
confidence: 55%
“…Of nine patients with recurrent or residual disease, only two patients were positive for EBV; therefore, scarring change after irradiation may reduce the overall ability of nasopharyngeal brushing to detect EBV positivity in patients with recurrent NPC. 25 However, the fact that 98% of the swab samples obtained successfully from the nasopharynx contained sufficient DNA for the amplification of the LMP-1 gene did not appear to be a problem in this study. One reason for this phenomenon may be that radiation-treated patients were encouraged to irrigate their nasopharynx vigorously, even during radiation treatment, to prevent crust formation.…”
Section: Discussionmentioning
confidence: 55%
“…The technique and procedure of the PCR for EBV and HPV DNA detection have been described previously. [17][18][19][20][21] Genomic regions in the EBNA-1 were amplified by primer sets of 5 0 -TGAATACCACCAAGAAGGTG-3 0 and 5 0 -AGTTCCTTCGTCGGTAGTC-3 0 or 5 0 -GTA-GAAGGCCATTTTTCCAC-3 0 and 5 0 -TTTCTACGT-GACTCCTAGCC-3 0 . Negative control samples containing water were also processed in parallel to tissue samples.…”
Section: Methodsmentioning
confidence: 99%
“…24,26 This may be because of insensitive, qualitative (multiplex) PCR assays 24 or insufficient brushing of the NP epithelium in these controls. In contrast, several other studies 25,45 and our present study using sensitive quantitative real-time PCR, have found EBV DNA in brushing specimens from most healthy carriers, albeit at low levels.…”
Section: Np Brushings Of Npc Patients Contain Extremely High Ebv Dna mentioning
confidence: 99%
“…This is indicated by recent reports, showing elevated EBV DNA loads in NP swab samples of NPC patients using nonstandardized PCR techniques. [24][25][26][27] Thus, we investigated in more detail the diagnostic value of EBV DNA load quantification and EBV mRNA detection, in particular BARF1 and EBNA1 mRNA, in NP brushing specimens from consecutive Indonesian ENT patients with suspected NPC and various controls. In all patients suspected for NPC a biopsy was taken from the same site to confirm presence or absence of NPC by using EBER in situ hybridisation (EBER-RISH) and immunohistochemical staining for EBNA1 and LMP1.…”
mentioning
confidence: 99%